GOVERNANCE IN MANAGING FAMILY ENTERPRISES - Raymond Win Sarta; Kartika Nuringsih (International Journal of Application on Economics and Business, 2026)
Succession to maintain a family company faces obstacles due to conflicts of interest among family members. Therefore, this study aims to determine the factors that influence internal conflicts in family business management in several enterprises in Jabodetabek. As a governance mechanism of family business management, two independent variables, namely emotional intelligence and perceived compliance with the code of ethics, are placed to identify this conflict. This study used convenience sampling involving 125 business owners as respondents. The businesses are small and medium-sized in food and beverage, fashion, beauty, and construction industries. The results of structural regression processing show that emotional intelligence has no significant effect on internal conflict, while the perceived compliance with the code of ethics has a positive and significant effect at the 5 percent level on internal conflict. Specifically, there is a controversy that the formation of perceptions of compliance with the code of ethics has the effect of triggering potential internal conflicts. The formation of opportunistic behavior tends to influence decision making so that the perception of compliance can trigger internal conflict. This effect needs to be considered by family business owners and managers to anticipate the possibility of conflict between family members.